KEMAMPUAN TRANSLASI REPRESENTASI MATEMATIS SISWADALAM MENYELESAIKAN SOAL MATERI HIMPUNANDI KELAS VIII SMPI - Wullandari, Della Riski; Halini, Halini; T, Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and Â describe the ability translation of the translation mathematical representation of students in solving material sets in grade VIII SMPI Husnul Yaqin. The subject in this research was 22 student in grade VIII SMPI Husnul Yaqin. Method used was descriptive in forrm survey.the technique used is measurement technique and direct comunication technique. The measurement such as written test that is the ability translation test of mathematical representation and the direct comuniccation technique such as interview. Based on the result in data analysis, overall the ability translation representation students included in high category. Mostly students do the translation from the verbal to the symbol.Keywords: Translation Ability, Representation, Sets.